Amine modification of nonporous silica nanoparticles reduces inflammatory response following intratracheal instillation in murine lungs. (22nd January 2016) - Morris, Angie S.; Adamcakova-Dodd, Andrea; Lehman, Sean E.; Wongrakpanich, Amaraporn; Thorne, Peter S.; Larsen, Sarah C.; Salem, Aliasger K.
Highlights: We investigated nonporous silica NPs both bare and modified with amine functional groups (3-aminopropyltriethoxysilane (APTES)) in order to evaluate the effect of surface chemistry on biocompatibility. No cytotoxicity was observed in a human lung cancer epithelial cell line (A549) for bare silica NPs or amine-functionalized silica NPs. Bare silica NPs elicited a significantly higher inflammatory response compared to amine-functionalized NPs. Abstract: Amorphous silica nanoparticles (NPs) possess unique material properties that make them ideal for many different applications. However, the impact of these materials on human and environmental health needs to be established. We investigated nonporous silica NPs both bare and modified with amine functional groups (3-aminopropyltriethoxysilane (APTES)) in order to evaluate the effect of surface chemistry on biocompatibility. In vitro data showed there to be little to no cytotoxicity in a human lung cancer epithelial cell line (A549) for bare silica NPs and amine-functionalized NPs using doses based on both mass concentration (below 200 μg/mL) and exposed total surface area (below 14 m 2 /L). To assess lung inflammation, C57BL/6 mice were administered bare or amine-functionalized silica NPs via intra-tracheal instillation. Two doses (0.1 and 0.5 mg NPs/mouse) were tested using the in vivo model. At the higher dose used, bare silica NPs elicited a significantly higher inflammatory response, as evidence by increased neutrophils and total protein in bronchoalveolar lavage (BAL) fluid compared to amine-functionalized NPs. From this study, we conclude that functionalization of nonporous silica NPs with APTES molecules reduces murine lung inflammation and improves the overall biocompatibility of the nanomaterial.